(untitled) (Journal of Biomedical Investigation, 2024)
Background: Diagnosis of prostatic tumours, especially the suspicious cases of precancerous lesions are usually subjective, using conventional morphology in Haematoxylin and Eosin stained tissue section. This method is also prone to diagnostic errors or misdiagnosis both in benign and malignant cases. Morphological investigation via light microscopy remains the gold standard for the diagnosis of prostatic carcinoma. Intra-observer variability in diagnosis and difficult cases may benefit from immunohistochemical staining using panel of markers. Aim: The potentials of p63 and α‑methylacyl CoA racemase (AMACR) in differentiating cases of benign prostatic hyperplasia (BPH) from prostate cancer was studied. Method: Eighty-five previously diagnosed archived prostate tumour tissues comprising of 41 malignant and 44 benign lesions were retrieved for the Histopathology Laboratory of a tertiary healthcare facility. The samples were reviewed and processed for immunostaining (IHC) using p63 and AMACR monoclonal antibodies. Results: There was 85.9% (73) agreement between morphological diagnosis using conventional Haematoxylin and Eosin technique and IHC, and 14.10% (12) discordance. Of this discordance, 4 (33.30%) were found in cancer of the prostate and 8 (66.70%) were found in benign prostatic hyperplasia; 37 (90.2%) of previously H&E diagnosed CAP showed strong (3+) immunoreactivity for AMACR while 4(9.8%) were positive for p63. Similarly, previously H&E diagnosed BPH showed 36(81.8%) strong immunoreactivity for p63 and 8(18.2%) for AMACR. Grade V cancers occurred highest with 41% while grade II was the lowest with 5% occurrence. The Gleason’s scores ranges for 4+4 to 5+5, while the age of patients ranges from 48 to 86 years with mean age of 68.3 years. Conclusion: Whereas morphological method remains the gold standard for diagnosis of prostatic lesions, it is not devoid of diagnostic errors. Therefore, p63 and AMACR biomarkers may be of great value in definitive diagnosis and confirming small foci of adenocarcinoma, resolving suspicious lesions and excluding benign mimickers.